Pertumbuhan dan Perkembangan Bibit Akor yang Diinokulasi Bakteri Patogen Terbawa Benih - Tati Suharti; Triwidodo Arwiyanto; Tri Joko (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Growth and Development of Inoculated in Northern Black Wattle Seedling with Seed Borne Bacterial PathogensNorthern black wattle (Acacia auriculiformis) is a fast growing species that has multipurpose benefits such as pulpwood, solid wood, firewood, charcoal and pellet. Seed-borne bacterial pathogens were reported to reduce seed germination and seedling growth. The objective of this study was to evaluate effect of seed borne bacterial pathogen of A. auriculiformis on seed germination and 12 weeks-old seedling growth. Bacterial seed inoculation was performed by soaking the seed into respective bacterial suspension for 2 hours. The tested bacteria were Acinetobacter sp., Alcaligenes faecalis, Burkholderia cepacia complex, Escherichia hermannii, Paenochrobactrum sp., Pseudomonas stutzeri, Ralstonia sp., and Salmonella bongori. The results showed that all tested bacteria could reduce seed germination, but those does not affect seedling growth significantly. All tested bacteria excluding Acinetobacter sp. could inhibit seedling growth and development.